2000
DOI: 10.1039/b005277i
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated formation of hydrogen spin adduct from phenylsilane. A new example of inverted spin trapping?

Abstract: Photodissociation of phenylsilane was studied by EPR spectroscopy using N-benzylidene-tert-butylamine N-oxide (PBN) and bis(benzene)chromium (BBC) as spin trapping systems. Under controlled UV irradiation and in the presence of dioxygen, hydrogen spin adducts were detected. Conditions for the formation and stability of the adducts have been studied. A mechanism involving "inverted spin trapping" was propounded that implies photoactivation of the spin traps followed by the formation of the superoxide radical io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results are summarised in Table 3 and compared to the available experimental values. 5,50 The most remarkable features of the data collected in this last table is that for all the theoretical methods hydrogen and chromium spin populations are in good agreement with experimental results.…”
Section: Bis(benzene) Chromium and Its Radical Cationsupporting
confidence: 67%
See 4 more Smart Citations
“…The results are summarised in Table 3 and compared to the available experimental values. 5,50 The most remarkable features of the data collected in this last table is that for all the theoretical methods hydrogen and chromium spin populations are in good agreement with experimental results.…”
Section: Bis(benzene) Chromium and Its Radical Cationsupporting
confidence: 67%
“…2 This proposed mechanism is supported by two experimental features: (i) the direct observation of the endo position of the isobutyronitril (R ¼ IBN) spin adduct by angle-selected ENDOR spectroscopy in frozen solution, 2 and (ii) the observation in liquid solution at room temperature of a dynamic interannular radical transfer between the two equivalent structures B and C (see Scheme 1), independently of the nature of the radical adduct. 2,4 A more detailed study of the hydrogen addition (R ¼ H) revealed that the mechanism is more complex than proposed in Scheme 1, and necessitates traces of oxygen and a low level of UV irradiation: 5 BBC !…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations